A Systematic Review and Meta-Analysis on Post-Abortion Contraceptive Utilization and Associated Factors in Ethiopia - Wake, Getu Engida; Fitie, Girma Wogie; Tizazu, Michael Amera (Frontiers in Public Health, 2022)
Background: Post-abortion contraceptive utilization is the initiation and use of family planning methods at the time of management of abortion or before fertility returns. A significant discrepancy was reported regarding the prevalence and its associated factors of post-abortion contraceptive utilization in Ethiopia. So, this systematic review and meta-analysis aimed to estimate the pooled prevalence of post-abortion contraceptive utilization and its associated factors in Ethiopia. Methods: Preferred reporting items for systematic reviews and meta-analysis (PRISMA) guideline was used. The databases such as; PubMed, Google Scholar, Science Direct, Cochrane library, Scopus, CINAHL, Web of Science, and additional searches by using direct Google search, libraries, and preprint were searched. Joanna Briggs institute meta-analysis of statistics assessment and review instrument (JBI-MAStARI) was used for critical appraisal. Results: A total of 17 studies with 13075 individuals were included. Of these, 14 studies with 5719 individuals were used to estimate the prevalence. The pooled prevalence of post-abortion contraceptive utilization in Ethiopia was 63.64% (95% CI: 57.75-69.53). The subgroup analysis reported the highest prevalence of post-abortion contraceptive utilization in a study conducted in Addis Ababa(77.40%), a study published during (2015-2021) (66.15%), and among studies with a sample size greater than 400 (66.84%). The pooled odds ratio (OR) of post-abortion contraceptive utilization for the mothers who had post-abortion family planning counseling was 4.15; (95% CI=1.30, 13.2), and history of family planning utilization was 4.28; (95% CI =2.66, 6.89). Conclusions: The pooled prevalence of utilization of post-abortion contraceptives in this meta-analysis remains low. Post-abortion family planning counseling and the history of the utilization of modern family planning methods were significantly associated with the practice of post-abortion contraceptives. Ministry of health should encourage post-abortion family planning utilization, making more efforts on post-abortion contraceptive counseling. Health facilities should work hard to strengthen the family planning counseling service, especially focusing on those who had no previous family planning utilization.